A parent's intuition is always right: Weighing intuitions in the debate over the nature of full moral status. (25th September 2021) - Graber, Abraham
Abstract: The debate over the grounds of full moral status relies heavily on the "method of cases." In the method of cases intuitions about particular cases are taken as evidence for philosophical theories. Much in the debate over the grounds of full moral status turns on our intuitions regarding the moral status of individuals with intellectual disability. This paper argues that the intuitions of those in close personal relationships with individuals with intellectual disability are more reliable than the intuitions of those who lack such a relationship. When theorizing about full moral status, we should privilege the intuitions of those who have a close personal relationship with an individual with intellectual disability.